Contributions of the theory of policy enactment: analysis based on a study on Special Education policies in the context of practice - Marilza Pavezi (Red Latinoamericana de Estudios Epistemológicos en Política Educativa, 2018)
This paper explores the main contributions of the theory of policy enactment authored by Ball, Maguire and Braun (2016). These contributions were developed from the use of this theory in the analysis of Policies for Special Education in the State of Alagoas, Brazil. The theory of policy enactment is seen to offer significant elements for a broad and contextualized analysis of educational policies in general.